PAIN RELIEVED USING EXTRA ANATOMY PATHWAY IN ACUTE INFECTION - Abdurachman, Abdurachman (Institute of Topical Disease Universitas Airlangga, 2012)
Acute infection is characterized especially by pain as major complaint of patients. In this following case report, it will be shown that pain cause of acute infection can be relieved using acupuncture technique. Acupuncture use meridian as extra anatomy pathway.